Automotive printed circuit boards recycling: an economic analysis. (10th May 2016) - Cucchiella, Federica; D'Adamo, Idiano; Rosa, Paolo; Terzi, Sergio
Abstract: End of Life Vehicles (ELVs), together with Waste from Electric and Electronic Equipments (WEEEs), are re-known as an important source of secondary raw materials. Since many years, their recovery allowed the restoring of great amounts of metals for new cars' production. However, the management of electronic systems embedded into ELVs is yet rarely considered by the scientific literature. The purpose of the paper is trying to fill in this gap through the proposition of an innovative economic model able to identify the presence of profitability within the recovery process of automotive Waste Printed Circuit Boards (WPCBs). Net Present Value (NPV) and Discounted Payback Time (DPBT) will be used to demonstrate the validity of investments in this type of plants. Furthermore, a sensitivity analysis on a set of critical variables (plant saturation level, gold (Au) content, Au market price, Au final purity level, WPCBs purchasing cost and opportunity cost) will be conducted for the evaluation of the impact of significant variations on results. Finally, the matching of predicted European ELVs volumes (during the period 2015–2030) and NPVs coming from the economic model will quantify the potential advantages coming from the implementation of this new kind of circular economy.